Interactive effects of nemarioc-al and nemafric-bl phytonematicides on growth and foliar nutrient elements of tomato cultivar 'HTX 14' plants - Maake, Mafutha Violet (My University, 2018)
The production of tomato (Solanum lycopersicum L.) plants had been crucial in various parts of the world since tomato fruit contribute widely to human health. However, most tomato cultivars had been shown to be highly susceptible to plant-parasitic nematodes, especially the root-knot (Meloidogyne species) nematodes. Two cucurbitacin-containing phytonematicides, namely, Nemarioc-AL and Nemafric-BL phytonematicides, manufactured from fruits of Cucumis species, are being researched and developed in South Africa as an alternative for management of Meloidogyne species. Most trials on tomato plants and cucurbitacin-containing phytonematicides had been under greenhouse conditions, with limited information on their interactive effects under microplot and field conditions. The objectives of this study were: (1) to determine the interactive effects of Nemarioc-AL and Nemafric-BL phytonematicides on growth and accumulation of nutrient elements in leaf tissues of tomato plants under microplot conditions and (2) to investigate the interactive effects of Nemarioc-AL and Nemafric-BL phytonematicides on growth and accumulation of nutrient elements in leaf tissues of tomato plants under field conditions. In the microplot study, uniform four-week-old tomato cv. 'HTX 14' seedlings were transplanted in 4 L plastic bags containing loam soil and Hygromix-T at the 3:1 ratio (v/v). Plastic bags were inserted into holes at 0.50 m inter-row spacing and 0.60 m intra-row spacing. The 2 x 2 factorial trial, with the first and second factors being Nemarioc-AL and Nemafric-BL phytonematicides, respectively, each at two levels. The four treatments, namely, AL0BL0, AL0AL1, BL0BL1 and AL1BL1, were arranged in a randomised complete block design. Treatments were xxiv applied seven days after transplanting and repeated weekly until harvest. Under field conditions, uniform four-week-old tomato cv. 'HTX 14' seedlings were transplanted into the field at 0.50 m inter-row spacing and 0.60 m intra-row spacing. Treatments, experimental designs and application interval were as those under microplot conditions. At 60 days after the treatments, seedlings AL × BL interaction was not significant on all plant variables in Experiment 1 under microplot conditions, whereas in Experiment 2 the interaction was highly significant (P ≤ 0.01) on dry shoot mass, contributing 72% in total treatment variation (TTV) of the variable. Relative to untreated control, the two-way matrix showed that the interaction reduced dry shoot mass by 8%. Nemarioc-AL phytonematicide had a significant (P ≤ 0.05) effect on stem diameter in Experiment 1 under field conditions, whereas Nemafric-BL phytonematicide had significant effects on plant height in Experiment 2, contributing 39 and 56% in TTV of the respective variables. Relative to untreated control, Nemarioc-AL phytonematicide increased stem diameter by 4%, whereas Nemafric-BL phytonematicide increased plant height by 2%. The interaction was also significant (P ≤ 0.05) on Na and S and highly significant (P ≤ 0.01) on Zn, contributing 76, 26 and 6%, respectively, in TTV of the respective variables in Experiment 1 under field conditions. Using a two-way matrix, the interaction increased Na and S by 12 and 41%, respectively, but reduced Zn by 52%. In Experiment 2, the interaction was highly significant (P ≤ 0.01) on P alone, contributing 16% in TTV of the variable, with the interaction reducing P by 76%. Nemarioc-AL phytonematicide had significant effects (P ≤ 0.05) on Ca and highly significant effects (P ≤ 0.01) on S, contributing 31 and 58% in TTV of the respective variables in Experiment 1. Relative to untreated control, Nemarioc-AL phytonematicide increased P by 39%. In xxv Experiment 2, Nemarioc-AL phytonematicide had significant effects on Ca and highly significant effects (P ≤ 0.01) on S, contributing 66 and 49% in TTV of the respective variables. Relative to untreated control, Nemarioc-AL phytonematicide reduced Ca by 19% and S by 36%, respectively. Nemafric-BL phytonematicide had a significant effect (P ≤ 0.05) on P, contributing 33% in TTV of the variable in Experiment 1. Relative to untreated control, Nemafric-BL phytonematicide increased P by 41%. In Experiment 2, Nemafric-BL phytonematicide had significant effects (P ≤ 0.05) on S, contributing 40% in TTV of the variable. Relative to untreated control, Nemafric-BL phytonematicide reduced S by 33%. At 74 days after initiating the treatments under field conditions, the interaction of Nemarioc-AL and Nemafric-BL phytonematicides were not significant for plant height, stem diameter, fresh fruit and dry shoot mass in both experiments. Nemarioc-AL phytonematicide was also not significant in all plant variables in both experiments. Effects of Nemafric-BL phytonematicide were highly significant on dry shoot mass in Experiment 1 and stem diameter in Experiment 2, contributing 60 and 67% in TTV of the respective variables. Relative to untreated control, Nemafric-BL phytonematicide reduced dry shoot mass by 28% and increased stem diameter by 11% in Experiment 1 and Experiment 2, respectively. The AL × BL interaction had significant effects (P ≤ 0.05) on P, contributing 57% in TTV of the variable in Experiment 1. Relative to untreated control, the interaction increased P by 12%. In Experiment 2, the interaction had significant effects (P ≤ 0.05) on K, Mg, S and Mn, contributing 78, 65, 74 and 68% in TTV of the respective variables. Using a two-way matrix, relative to untreated control, the interaction increased K by 8%, but reduced Mg, Mn and S by 14, 82 and 1%, respectively. Nemarioc-AL phytonematicide was not significant in both the xxvi experiments, whereas Nemafric-BL phytonematicide had significant effects on Mg in Experiment 1, contributing 68% in TTV of the variable. Relative to untreated control, Nemafric-BL phytonematicide increased Mg by 15%. In conclusion, the interaction of Nemarioc-AL and Nemafric-BL phytonematicides were not compatible with each other as they had undesirable effects on growth of tomato plants and accumulation of most essential nutrient elements in leaf tissues of this plant.
Thesis (MSc. Agriculture (Horticulture)) -- University of Limpopo, 2018
Keywords: Plant-parasitic nematodes; Tomato production; Phytonematicides; Root-knot nematodes; Plant nematodes; Tomatoes -- Breeding